The acute effects of vaporized cannabis on drivers’ hazard perception and risk-taking behaviors in medicinal patients: A within-subjects experiment - Schiemer, Carla; Horswill, Mark S.; Hill, Andrew; Summers, Mathew J.; Stefanidis, Kayla B. (Journal of safety research, 2025)
•No changes in performance on video-based tasks after consuming prescribed cannabis.•Perceived hazard perception task performance was reduced.•Perceived on-road traffic conflict prediction ability was reduced.•No association between objective and subjective hazard perception performance. Introduction: As the medically prescribed use of cannabis flower continues to increase, there is a need to understand how vaporized cannabis can acutely affect driving-related skills and risk-taking behaviors in medicinal populations. Method: Given this, the present study examined the acute effects of vaporized cannabis flower on measures of hazard perception, driving-related risk-taking behaviors, and subjective perceptions of driving skills in a sample of adult medicinal cannabis patients. Participants (N = 38, M age = 43) attended both a baseline (no cannabis) and intervention appointment (with cannabis consumption), where they completed video-based tasks and self-report measures of driving ability. Results: After vaporizing one dose of their prescribed cannabis flower, participants exhibited no significant changes in performance on any of the video-based tasks (hazard perception skill, gap acceptance, following distance or speed) compared to baseline. However, cannabis consumption resulted in significant reductions in perceived hazard perception task performance and on-road traffic conflict prediction ability. Furthermore, there was a lack of association between objective and subjective hazard perception performance at both time points. Practical applications: These results suggest that while acute prescribed cannabis consumption may reduce appraisals of selected skills, overall hazard perception ability and driving-related risk-taking behavior may remain unchanged.